CIRCULATING ANTIBODIES TO ERYTHROPOIETIN ARE ASSOCIATED WITH LOWER EFFICACY OF RECOMBINANT EPOETIN TREATMENT IN PATIENTS UNDERGOING HAEMODIALYSIS - V. D. Nazarov; S. V. Lapin; V. A. Dobronravov; K. A. Smirnov; D. A. Mayer; T. O. Muzhetskaya; A. A. Totolian (Медицинская иммунология, 2018)
Biological preparations (BP) obtained by gene engineering possess a special characteristic called immunogenicity, i.e. propensity of biological drugs to induce an undesired immune response associated with arising anti-drug antibodies. These antibodies can change BP pharmacokinetics and pharmacodynamics, and therapeutical efficacy. A significant proportion of hemodialysis patients with end-stage renal disease treated by recombinant erythropoietin (rEPO) have clinical features of resistance to such therapy. The aim of the study was to investigate whether anti-rEPO antibodies are associated with hemoglobin concentrations (Hb) and red blood cells counts (RBC) in hemodialysis patients, receiving long-term rEPO therapy. This research was performed at the Research Institute of Nephrology at the First St. Petersburg I.Pavlov State Medical University. Thirty-seven hemodialysis patients (pts) with end-stage renal disease and anemia treated with different rEPO formulations were included into the study. The patients were further divided into two groups: those with diminished and normal clinical response to rEPO therapy (DCR, n = 21 vs NCR group, n = 16, respectively). To determine threshold levels of antibodies to rEPO-beta (Roche, Switzerland) we tested blood serum samples of 35 healthy blood donors who never received rEPO in the past. Concentration of antibodies was measured by means of dot-blot method. The threshold antibody concentrations were defined by measurement of anti-rEPO concentrations in 2-fold stepwise dilutions (1:10 to 1:200) of blood sera from 35 healthy donors .The threshold value for rEPO-binding antibodies was 20.27 µg/ml (95 CI%±0.43). Antibodies to rEPO were found in 54 % of serum samples in the patients. Anti-rEPO antibodies concentrations correlated with mean values of hemoglobin and erythrocyte counts over a period of 12-months for the entire group of hemodialysis patients (r = -0.368, p = 0.025 and r = -0.336, p = 0.042 respectively). Concentration of anti-rEPO antibodies, and the mean weekly rEPO dose were significantly higher in DCR group, compared to NCR group (p = 0.0019). In conclusion, higher levels of anti-rEPO binding antibodies seem to be associated with decreased therapeutic response to the clinically applied rEPO formulations.